Can the glyphosate herbicide cause behavioral changes in worker bees? (Research, Society and Development, 2023)
The objective of this study was to observe possible behavioral alterations of Africanized bees (Apis mellifera Linnaeus, 1758) after exposure to glyphosate herbicide. For this, two exposure methods were used (ingestion and spraying) and concentrations of 0 (Control Group), 0.01 and 1 mL.L-1 during 24 hours of exposure. In the ingestion method, the bees were fed with honey added to the solutions, while in the contact test, the bees were sprayed with the herbicide concentrations. Contact interactions (antennation and trofalaxis), mobility (ability to take off) and lethargy (difficulty taking off and poor flight) were analyzed, in addition to individual mortality. In general, in both types of exposure (ingestion and spraying), at the lowest concentration tested (0.01 mL.L-1) higher frequency of contact and lower mobility of bees were observed. While bees exposed to 1 mL.L-1 of glyphosate showed less contact and greater mobility and lethargy, in addition to a higher bee mortality rate. It was confirmed that higher concentrations of the herbicide can affect the social interactions of bees; however, the spraying method was the one that led to the highest mortality. Thus, we conclude that exposure to glyphosate causes effects on social interactions in individuals of A. mellifera.